The Belgian Virtual Tumorbank: A Tool for Translational Cancer Research - Vande Loock, Kim; Van der Stock, Eva; Debucquoy, Annelies; Emmerechts, Katia; Van Damme, Nancy; Marbaix, Etienne (Frontiers in Medicine, 2019)
Background: Biobanks play a critical role in cancer research by providing high quality biological samples for research. However, the availability of tumor samples in single research institutions is often limited, especially for rare cancers. In order to facilitate the search for samples scattered among different Belgian institutions, a nationwide virtual tumorbank project was launched and is operational since February 2012. The Belgian Virtual Tumorbank (BVT) network encompasses the tumor biobanks from eleven Belgian university hospitals that collect and store residual human tumor samples locally and is coordinated by the Belgian Cancer Registry. Material & Methods: A web application was developed and consists of two modules. The registration module (BVTr) centralises the tumor sample data from the local partner biobanks. The catalogue module (BVTc) allows researchers to trace the tumor samples in the eleven tumor biobanks. The BVTc contains patient, medical and technical data, but excludes identifying information to ensure privacy of individuals. Automatic and manual controls guarantee high quality data on the samples requested by scientists for research purposes in oncology. A major advantage of the BVT network is that the available data can be linked to the data of the Belgian Cancer Registry for quality control purposes. Results: Currently, more than 92,000 registrations are available in the catalogue. Twenty-seven % of the residual primary tumor samples originate from breast tissue, but also less frequent localisations such as head and neck (4%), male genital organs (1,7%) and urinary tract (1%) are available. In addition to the residual tumor tissue samples, also other available material can be stored and registered by the local biobanks. The most common type is corresponding normal tissue (19%).Other frequently available materials are plasma, blood, serum, DNA and buffy coat. Even PBMCs, RNA, cytology and urine are available in some cases. Discussion & Conclusion: The BVT catalogue is a valuable source of information for oncology research and the ultimate goal is to promote multidisciplinary cancer research (i.e. pathogenesis, disease prediction, prevention, diagnosis, treatment and prognosis) for the benefit of all cancer patients.